Building Human Visual Attention Map for Construction Equipment Teleoperation - Fan, Jiamin; Li, Xiaomeng; Su, Xing (Frontiers in Neuroscience, 2022)
Construction equipment teleoperation is a promising solution when the site environment is hazardous to operators. However, limited situational awareness of the operator exists as one of the major bottlenecks for the implementation. Virtual annotations (VAs) can use simple and clear symbols to convey information of operating clues, thus improving an operator's situational awareness without introducing an overwhelming cognitive load. It is of primary importance to understand how an operator's visual system responds to different VAs from a human-centered perspective. This study investigates the effect of VA on teleoperation performance during an excavating task. A visual attention map is generated to describe how a VA's parameters, such as location and size, influence an operator's attention to and understanding of the VA. The result of this study can improve the understanding of how human vision works in virtual or augmented reality. It also offers guidance on the practical implication of designing a more friendly teleoperation system.